Engineering synucleinopathy‐resistant human dopaminergic neurons by CRISPR‐mediated deletion of the SNCA gene. (21st December 2018) - Chen, Yixi; Dolt, Karamjit Singh; Kriek, Marco; Baker, Terry; Downey, Patrick; Drummond, Nicola J.; Canham, Maurice A.; Natalwala, Ammar; Rosser, Susan; Kunath, Tilo
Abstract: An emerging treatment for Parkinson's disease (PD) is cell replacement therapy. Authentic midbrain dopaminergic (mDA) neuronal precursors can be differentiated from human embryonic stem cells (hESCs) and human induced pluripotent stem cells (iPSCs). These laboratory‐generated mDA cells have been demonstrated to mature into functional dopaminergic neurons upon transplantation into preclinical models of PD. However, clinical trials with human fetal mesenchephalic cells have shown that cell replacement grafts in PD are susceptible to Lewy body formation suggesting host‐to‐graft transfer of α‐synuclein pathology. Here, we have used CRISPR/Cas9n technology to delete the endogenous SNCA gene, encoding for α‐synuclein, in a clinical‐grade hESC line to generate SNCA +/− and SNCA −/− cell lines. These hESC lines were first differentiated into mDA neurons, and then challenged with recombinant α‐synuclein preformed fibrils (PFFs) to seed the formation for Lewy‐like pathology as measured by phosphorylation of serine‐129 of α‐synuclein (pS129‐αSyn). Wild‐type neurons were fully susceptible to the formation of protein aggregates positive for pS129‐αSyn, while SNCA +/− and SNCA −/− neurons exhibited significant resistance to the formation of this pathological mark. This work demonstrates that reducing or completely removing SNCA alleles by CRISPR/Cas9n‐mediated gene editing confers a measure of resistance to Lewy pathology. Abstract : CRISPR/Cas9n was used to delete the SNCA gene in human embryonic stem cells (hESCs) to generate SNCA +/− and SNCA −/− cell lines. They exhibited a similar marker profile to wild‐type dopaminergic neurons. All genotypes of neurons were treated with α‐synuclein preformed fibrils (PFFs), but only wild‐type neurons had significant Lewy‐like pathology as measured phospho‐serine‐129 α‐synuclein (pS129‐αSyn), suggesting SNCA −/− neurons would be resistant to Parkinson's disease.